Law Enforcement Obstacle Against Online Gambling at Lampung Regional Police - Andri Wetson. R. (Ius Poenale, 2021)
Easy access to the world of information technology currently impacts the rise of cybercrime, including the crime of online gambling. Many efforts have been made by the government and law enforcers, including, in this case, the police, to prevent and take action against this online gambling crime, either block sites that are gambling arenas or improve the national security system to stop these gambling sites. This research aims to look at law enforcement against online gambling crimes in Bandar Lampung City and determine the factors that became an obstacle in law enforcement of online gambling crimes at Lampung Regional Police. This research method uses a normative juridical approach. Based on the discussion and research results, law enforcement against online gambling crimes in Bandar Lampung City is carried out by applying the instrument of Article 303 of the Criminal Code rather than Article 27 Paragraph (2) Jo. Article 45 of the ITE Law. The research also shows the factors that became an obstacle in law enforcement of online gambling crimes at Lampung Regional Police are: (1) Longer Detention Period for Online Gambling Crimes in the Criminal Code Instruments than the Gambling Control Act, (2) Lack of Investigators' Awareness in Information Technology, (3) Use of Electronic Evidence Requires Expert Information is inhibiting law enforcement against online gambling crimes in Bandar Lampung. Suggestions from the research are to conduct information technology guidance training to the Bandar Lampung Police Investigation and Criminal Unit.